Photothermal Regenerated Fibers with Enhanced Toughness: Silk Fibroin/MoS2 Nanoparticles - Jianjun Guo (MDPI AG, 2021)
The distinctive mechanical and photothermal properties of Molybdenum sulfide (MoS2) have the potential for improving the functionality and utilization of silk products in various sectors. This paper reports on the preparation of regenerated silk fibroin/molybdenum disulfide (RSF/MoS2) nanoparticles hybrid fiber with different MoS2 nanoparticles contents by wet spinning. The simulated sunlight test indicated that the temperature of 2 wt% RSF/MoS2 nanoparticles hybrid fibers could rise from 20.0 °C to 81.0 °C in 1 min and 98.6 °C in 10 min, exhibiting good thermal stability. It was also demonstrated that fabrics made by manual blending portrayed excellent photothermal properties. The addition of MoS2 nanoparticles could improve the toughness of hybrid fibers, which may be since the mixing of MoS2 nanoparticles hindered the self-assembly of β-sheets in RSF solution in a concentration-dependent manner because RSF/MoS2 nanoparticles hybrid fibers showed a lower β-sheet content, crystallinity, and smaller crystallite size. This study describes a new way of producing high toughness and photothermal properties fibers for multifunctional fibers’ applications.